2017
DOI: 10.3390/ijerph14060565
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences of Arterial Stiffness and Arterial Age in Smokers

Abstract: The present study aimed to find gender differences for arterial stiffness and arterial aging in smokers. A total of 147 smokers (71 male and 76 female, matched for age) were explored using an Arteriograph in a cross-sectional survey. Pulse wave velocity (PWV), arterial age (AA), brachial and aortic augmentation index (AixBrach, AixAo), and blood pressure variables were assessed. Data about smoking intensity, such as the number of cigarettes smoked daily, smoking period, and smoking pack years (SPY) were used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
1
25
1
1
Order By: Relevance
“…However, the literature shows directly influence of smoking on vascular stiffness and arterial age of increased values of serum lipids, continuous activation of sympathetic nervous system and the rise of blood pressure. These chronic modifications associated to smoking leads to an increased risk of cardiovascular disease [ 26]. Our studied population was asymptomatic smoking young adults; however, they already presented reduced value of volume parameter.…”
Section: Discussionmentioning
confidence: 91%
“…However, the literature shows directly influence of smoking on vascular stiffness and arterial age of increased values of serum lipids, continuous activation of sympathetic nervous system and the rise of blood pressure. These chronic modifications associated to smoking leads to an increased risk of cardiovascular disease [ 26]. Our studied population was asymptomatic smoking young adults; however, they already presented reduced value of volume parameter.…”
Section: Discussionmentioning
confidence: 91%
“…First, this was a retrospective study and a relatively small number of male smokers were enrolled; thus, the data may be biased. A previous study indicated that arterial stiffness was significantly different between male and female smokers . Second, we may have underestimated the prevalence of smoking and the possibility of misclassification of smoker and non‐smoker groups.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that arterial stiffness was significantly different between male and female smokers. 34 Second, we may have underestimated the prevalence of smoking and the possibility of misclassification of smoker and nonsmoker groups. Many studies have indicated a problem with underestimation in self-reported smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation are responsible for a reduced level of antioxidants (Kim et al, 2010 ). Smoking is a potent oxidative stressor, able to impair arterial elasticity and endothelial function (Kim et al, 2010 ; Mozos et al, 2017b ), and lycopene was the only major serum carotenoid able to reduce the atherosclerotic risk in current and former smokers according to the Rotterdam Study (Klipstein-Grobusch et al, 2000 ).…”
Section: Lycopenementioning
confidence: 99%